Peran Pendidikan Sufistik dalam Diseminasi Keberagamaan Moderat bagi Peserta Didik - Huda, Khusnul (Sekolah Tinggi Agama Islam (STAI) Ki Ageng Pekalongan, Indonesia, 2024)
This study aims to describe the urgency of Sufistic education in shaping moderate religiosity for students. This qualitative research in the form of a literature study uses a descriptive approach. The research data uses various scientific literature that correlates with the subject matter. Meanwhile, data analysis uses the stages of reduction, presentation, and verification. The results of this study conclude that Sufistic education has urgency in shaping moderate religiosity for students. This can be manifested through a learning process that prioritises the intellectual, emotional and spiritual intelligence of students. This research contributes to the importance of Sufistic education values in internalising the values of forming moderate religiosity.